Chronic intermittent tachypacing by an optogenetic approach induces arrhythmia vulnerability in human engineered heart tissue. Issue 8 (9th October 2019) - Lemme, Marta; Braren, Ingke; Prondzynski, Maksymilian; Aksehirlioglu, Bülent; Ulmer, Bärbel M; Schulze, Mirja L; Ismaili, Djemail; Meyer, Christian; Hansen, Arne; Christ, Torsten; Lemoine, Marc D; Eschenhagen, Thomas
Abstract: Aims: Chronic tachypacing is commonly used in animals to induce cardiac dysfunction and to study mechanisms of heart failure and arrhythmogenesis. Human induced pluripotent stem cells (hiPSC) may replace animal models to overcome species differences and ethical problems. Here, 3D engineered heart tissue (EHT) was used to investigate the effect of chronic tachypacing on hiPSC-cardiomyocytes (hiPSC-CMs). Methods and results: To avoid cell toxicity by electrical pacing, we developed an optogenetic approach. EHTs were transduced with lentivirus expressing channelrhodopsin-2 (H134R) and stimulated by 15 s bursts of blue light pulses (0.3 mW/mm 2, 30 ms, 3 Hz) separated by 15 s without pacing for 3 weeks. Chronic optical tachypacing did not affect contractile peak force, but induced faster contraction kinetics, shorter action potentials, and shorter effective refractory periods. This electrical remodelling increased vulnerability to tachycardia episodes upon electrical burst pacing. Lower calsequestrin 2 protein levels, faster diastolic depolarization (DD) and efficacy of JTV-519 (46% at 1 µmol/L) to terminate tachycardia indicate alterations of Ca 2+ handling being part of the underlying mechanism. However, other antiarrhythmic compounds like flecainide (69% at 1 µmol/L) and E-4031 (100% at 1 µmol/L) were also effective, but not ivabradine (1 µmol/L) or SEA0400 (10 µmol/L). Conclusion: We demonstrated a high vulnerability to tachycardia of optically tachypaced hiPSC-CMs in EHT and the effective termination by ryanodine receptor stabilization, sodium or hERG potassium channel inhibition. This new model might serve as a preclinical tool to test antiarrhythmic drugs increasing the insight in treating ventricular tachycardia. Graphical Abstract: